Analysis of physicochemical and microbiological characteristics of Surinsar Lake in UT of Jammu & Kashmir, India - Yadav, Arvind Kumar; Mahajan, Arushi; Sharma, Tania; Bhushan, Indu; Mohd Noor, Ikhwan Syafiq; Yahya, Muhd Zu Azhan (John Wiley and Sons Inc, 2025)
Water in biological systems is not just a passive solvent but also plays a crucial role in the structure of proteins and nucleic acids, ensuring stability and flexibility. Macromolecules affect the state of water contacting them, affecting its order. Surinsar lake, a twin of Mansar Lake in Jammu, is experiencing deteriorating water quality due to human interference. A study examining ten locations found mean values for temperature, pH, conductivity, TDS, TSS, DO, BOD5, COD, total hardness, total alkalinity, chloride, sulfate, nitrate, oil and grease, turbidity, and faecal coliform. The findings call for new conservation policies.